ANTIMICROBIAL FINISHING ON 100% COTTON FABRIC BY USING STEM OF ABUTILON INDICUM - M, Jayakumari.; R, Divya . (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Abutilon indicum (Linn) family Malvaceae, commonly known as Atibala is an important medicinal plant. The whole plant as well as specific part such as root, leaves, and flowers is used to treat various healthy aliments skin treatment. It is found as a weed in sub Himalayan tracts, hills up to 1200m and in hotter parts of india. The plant is found to possess immunodulatory, anticonvulsant, larvicidal, lipid lowering, diuretic, and anti-ulcer activity. The plant contains antimicrobial activity in nature.The stem of the plant was shade dried and powdered to test the presence of antimicrobial activity . This study reveals the effect of antimicrobial activity and antifungal activity of the abutilon indicum plant extract on cotton fabric.